The DNA methylation landscape of human early embryos - Guo, Hongshan; Zhu, Ping; Yan, Liying; Li, Rong; Hu, Boqiang; Lian, Ying; Yan, Jie; Ren, Xiulian; Lin, Shengli; Li, Junsheng; Jin, Xiaohu; Shi, Xiaodan; et al. (Nature (London), 2014)
Base-resolution maps of DNA methylation in human gametes and early embryos offer novel insights into human methylation dynamics and the functional relationship between DNA methylation and gene expression. DNA methylation in the early embryo Global patterns of DNA methylation are drastically reprogrammed in primordial germ cells and early embryonic development in mammals. This reprogramming has been well characterized in mouse embryos, but a detailed understanding of DNA methylation dynamics in human embryos is lacking. Two papers published this week [in this issue of Nature ] reveal there is a massive loss of DNA methylation from most of the human genome immediately after fertilization, confirming that this epigenetic reprogramming is an evolutionarily conserved feature of development. Hongshan Guo et al . produced base-resolution maps of DNA methylation for human gametes and at several developmental stages of embryogenesis. Zachary Smith et al . obtained similar maps of DNA methylation at several developmental stages of early human embryogenesis and during derivation of human embryonic stem cell lines. The studies provide insights into differences between mouse and human methylation dynamics and the functional relationship between DNA methylation and the expression of genes and transposable elements. DNA methylation is a crucial element in the epigenetic regulation of mammalian embryonic development 1 , 2 , 3 , 4 , 5 . However, its dynamic patterns have not been analysed at the genome scale in human pre-implantation embryos due to technical difficulties and the scarcity of required materials. Here we systematically profile the methylome of human early embryos from the zygotic stage through to post-implantation by reduced representation bisulphite sequencing and whole-genome bisulphite sequencing. We show that the major wave of genome-wide demethylation is complete at the 2-cell stage, contrary to previous observations in mice. Moreover, the demethylation of the paternal genome is much faster than that of the maternal genome, and by the end of the zygotic stage the genome-wide methylation level in male pronuclei is already lower than that in female pronuclei. The inverse correlation between promoter methylation and gene expression gradually strengthens during early embryonic development, reaching its peak at the post-implantation stage. Furthermore, we show that active genes, with the trimethylation of histone H3 at lysine 4 (H3K4me3) mark at the promoter regions in pluripotent human embryonic stem cells, are essentially devoid of DNA methylation in both mature gametes and throughout pre-implantation development. Finally, we also show that long interspersed nuclear elements or short interspersed nuclear elements that are evolutionarily young are demethylated to a milder extent compared to older elements in the same family and have higher abundance of transcripts, indicating that early embryos tend to retain higher residual methylation at the evolutionarily younger and more active transposable elements. Our work provides insights into the critical features of the methylome of human early embryos, as well as its functional relation to the regulation of gene expression and the repression of transposable elements.